2022
DOI: 10.12911/22998993/144422
|View full text |Cite
|
Sign up to set email alerts
|

Finding Strategies for Peatland Rehabilitation; Agroforestry Systems on Various Types of Peat Depth in Three Villages in Central Kalimantan

Abstract: Peatland rehabilitation is an urgent need in order to minimize the effects of peat degradation and to support climate change mitigation. However, the rehabilitation of degraded peatlands still faces many obstacles. This study aimed to study the agroforestry system on peatlands applied by traditional communities as an effort to discover a peatland rehabilitation strategy. This research was conducted in the Pilang, Tanjung Taruna, and Kalampangan villages from February to August 2019. The data in this study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Agroforestry in peatland is also not new because it has been practiced in other areas. For example, Rotinsulu et al [46] said six agroforestry systems were found in various peat depths in Central Kalimantan. Farmers cultivate vegetable and fruitbased agroforestry on shallow peat, annual crops and fruit on medium peat, and fruit and rubberbased agroforestry on deep peat.…”
Section: Discussionmentioning
confidence: 99%
“…Agroforestry in peatland is also not new because it has been practiced in other areas. For example, Rotinsulu et al [46] said six agroforestry systems were found in various peat depths in Central Kalimantan. Farmers cultivate vegetable and fruitbased agroforestry on shallow peat, annual crops and fruit on medium peat, and fruit and rubberbased agroforestry on deep peat.…”
Section: Discussionmentioning
confidence: 99%